Ethyl ferulate liposome as well as preparation method and application thereof in resisting soft rot of kiwi fruits
By preparing ethyl ferulic acid nanoliposomes, the problem of antibacterial activity against postharvest soft rot in kiwifruit was solved, achieving highly efficient antibacterial and slow-release effects, significantly reducing the growth of *Gyrophyllaria media*, and improving the storage stability of the fruit.
Patent Information
- Application Number
- CN202511250448.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-11-28
AI Technical Summary
Kiwifruit has a high incidence of postharvest soft rot, and existing technologies are insufficient to effectively inhibit the growth of *Botrytis cinerea*, affecting the storage and sale of the fruit.
Ethyl ferulic acid nanoliposomes were prepared by melt emulsification and ultrasonication. Cholesterol or glyceryl distearate was used as the wall material, glyceryl caprylate was used as the liquid oil, and ethyl ferulic acid was encapsulated as the core material to form nanoliposomes with uniform particle size and stability for use as antibacterial agents.
It enhanced the antibacterial activity of ethyl ferulic acid, inhibited the growth of Staphylococcus aureus, the pathogen causing soft rot in kiwifruit, reduced the incidence of disease, achieved an inhibition rate of 90.15%, and had a sustained-release effect, with a cumulative release rate of 64.17% over 24 hours.
Smart Images

Figure CN121014728A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of food materials and the technical field of bacteriostatic preservation of agricultural products, and particularly relates to ferulic acid ethyl ester liposomes, a preparation method thereof and application of the ferulic acid ethyl ester liposomes in resisting soft rot of kiwifruit. BACKGROUND
[0002] Ferulic acid (FA) is a natural polyphenol antioxidant, which is almost insoluble in cold water, soluble in hot water, and easily soluble in organic solvents such as ethanol, and widely exists in crops such as soybeans, wheat, corn and sugarcane. As a free radical scavenger, FA can prevent the accumulation of reactive oxygen species (ROS) in the body, and is widely used in the fields of cosmetics and medicine, and has a protective and anti-aging effect on the skin. In addition, the ability of FA to inhibit fatty acid peroxidation and the growth of bacteria, fungi and yeasts can be used as a natural food preservative. Ferulic acid methyl ester (FAM) and ferulic acid ethyl ester (FAE) are two ester derivatives of FA, and have similar physicochemical properties and physiological effects as FA. Studies have reported that derivatives of phenolic acids have stronger antibacterial activity than free phenolic acids, and are applied to the prevention and control of postharvest fungal diseases of fruits and vegetables, and can be directly applied to the injury of fruits or combined with chitosan coating to show antifungal activity.
[0003] Nanoliposomes (NLP) are the second generation of solid lipid nanoparticles, which are multifunctional carriers composed of solid and liquid lipids as core matrix. Compared with traditional carriers, NLP has the advantages of increasing solubility, enhancing storage stability, improving permeability, bioavailability and prolonging the action time of drugs. Therefore, NLP has been widely used in the delivery of hydrophobic bioactive compounds.
[0004] Kiwifruit contains rich nutrients and is widely favored by consumers due to its unique flavor and taste. Kiwifruit belongs to the typical respiratory climacteric fruit and has a clear postharvest ripening process. It is prone to rot and softening due to respiration, mechanical damage and microbial infection after harvest, which leads to changes in taste, flavor and nutritional value, and poses a serious challenge to its storage, transportation and sales. The incidence of postharvest soft rot of commercial kiwifruit is high (the incidence during storage can be more than 50%), and Botryosphaeria dothidea is the pathogenic bacterium of soft rot. Botryosphaeria dothidea It is necessary to develop a green bacteriostatic agent that can inhibit the pathogenic bacterium of postharvest kiwifruit soft rot in combination with the actual production, so as to reduce the incidence of postharvest soft rot of kiwifruit. SUMMARY
[0005] The present application aims to provide a ferulic acid compound nanoliposome to overcome the shortcomings of ethyl ferulate as an antibacterial agent.
[0006] The first object of the present application is to provide a preparation method of ethyl ferulate liposome, comprising the following steps: S1. heating solid oil, liquid oil and ethyl ferulate at 73±1 DEG C for 10-15 min to a molten state, and keeping warm to obtain an oil phase; the mass ratio of solid oil, liquid oil and ethyl ferulate is 1:1:0.25-4; S2. preparing a 3% Tween-80 aqueous solution, heating to 73±1 DEG C, and stirring at 1000 rpm for 10 min to obtain an aqueous phase; S3. under the condition of 73±1 DEG C, adding 9.4-9.775 parts by mass of the aqueous phase dropwise into 0.225-0.6 parts by mass of the oil phase, stirring for 10 min, ultrasonic dispersion for 10 min, ice bath cooling and solidification for 30 min to obtain ethyl ferulate liposome.
[0007] Preferably, the method comprises the following steps: S1. heating solid oil, liquid oil and ethyl ferulate at 73±1 DEG C for 10-15 min to a molten state, and keeping warm to obtain an oil phase; the mass ratio of solid oil, liquid oil and ethyl ferulate is 1:1:2; S2. preparing a 3% Tween-80 aqueous solution, heating to 73±1 DEG C, and stirring at 1000 rpm for 10 min to obtain an aqueous phase; S3. under the condition of 73±1 DEG C, adding 9.6 parts by mass of the aqueous phase dropwise into 0.4 parts by mass of the oil phase, stirring for 10 min, ultrasonic dispersion for 10 min, ice bath cooling and solidification for 30 min to obtain ethyl ferulate liposome.
[0008] Preferably, the solid oil is cholesterol or glycerol bis-stearate, and the liquid oil is soybean phosphatidylcholine or glyceryl caprylate.
[0009] Preferably, the solid oil is glycerol bis-stearate, and the liquid oil is glyceryl caprylate.
[0010] The second object of the present application is to provide ethyl ferulate liposome prepared according to the method.
[0011] The third object of the present application is to provide an antibacterial agent taking the ethyl ferulate liposome as an active ingredient.
[0012] Preferably, the concentration of ethyl ferulate liposome is 0.25%-2% by mass fraction.
[0013] Preferably, the concentration of ethyl ferulate plasmid is 2% by mass fraction.
[0014] A fourth object of the present application is to provide the ethyl ferulate liposome or the bacteriostatic agent for use in the prevention of soft rot of kiwifruit.
[0015] Preferably, the use is the use of the ethyl ferulate liposome or the bacteriostatic agent in the inhibition of Botryosphaeria dothidea, which is the pathogenic bacterium of soft rot of kiwifruit.
[0016] The present application has the following beneficial effects: The present application uses the melt emulsification ultrasonic method to prepare ethyl ferulate nanoliposomes. With the entrapment efficiency and particle size of ethyl ferulate nanoliposomes as the main evaluation indexes, the effects of different wall materials and core material contents on the preparation of ethyl ferulate nanoliposomes are investigated. The ethyl ferulate liposomes prepared by using glyceryl stearate and glyceryl caprylate as wall materials have uniform particle size and stability. When the dosage of ethyl ferulate is 2% by mass fraction, the ethyl ferulate liposomes have uniform particle size and stability. The entrapment efficiency of 2% by mass fraction of ethyl ferulate nanoliposomes is 96.69 ± 0.71%, and the particle size, Zeta potential and polydispersity coefficient are 121.4 ± 0.96 nm, -58.3367 ± 1.37 mV and 0.1754 ± 0.001, respectively. The ethyl ferulate nanoliposomes can improve the antibacterial activity of ethyl ferulate, inhibit the growth of Botryosphaeria dothidea, the pathogenic bacterium of soft rot of kiwifruit, reduce the incidence, and the inhibition rate is 90.15 ± 0.90%. The ethyl ferulate nanoliposomes also have a certain sustained-release effect, and the cumulative release rate in vitro is 64.17% in 24 h. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro. B. dothidea Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro.
[0018] Figure 2 Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro.
[0019] Figure 3 Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro.
[0020] Figure 4 Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro.
[0021] Figure 5 Effects of different concentrations of ferulic acid (FA), methyl ferulate (FAM) and ethyl ferulate (FAE) on the growth of Botryosphaeria dothidea in vitro.
[0022] Figure 6 Thermogravimetric analysis of ethyl ferulic acid nanoliposomes; A (TGA curve) and B (DTG curve) illustrate the weight change of the sample and the relationship between the weight change rate and temperature, respectively.
[0023] Figure 7 Fourier transform infrared spectroscopy analysis of ethyl ferulic acid nanoliposomes.
[0024] Figure 8 To assess the physical stability of ethyl ferulic acid nanoliposomes.
[0025] Figure 9 The in vitro release curve of ethyl ferulic acid nanoliposomes is shown.
[0026] Figure 10 The in vitro antibacterial activity of ethyl ferulic acid nanoliposomes is shown in Figure A; A represents the colony diameter results of different material treatments, B represents the antibacterial rate results of different materials, and C represents the phenotypic diagram of colonies treated with different materials. Detailed Implementation
[0027] The following embodiments are further illustrations of the present invention, but not limitations thereof.
[0028] Example 1: Screening for ferulic acid compounds with the highest antibacterial activity The effects of ferulic acid (FA), methyl ferulic acid (FAM), and ethyl ferulic acid (FAE) on Staphylococcus aureus (Staphylococcus) were determined using the agar dilution method. Botryosphaeria dothidea (China Industrial Microbial Culture Collection Center, strain preservation number: CPCC 810148) Effect on mycelial growth. First, FA, FAM, and FAE were added to PDA medium that had been sterilized and cooled to approximately 50°C, respectively, to prepare drug-containing PDA medium with final concentrations of 0 (control group, CK), 100, 200, 400, and 800 mg / L. Then, 20 mL of drug-containing PDA medium was poured into sterile Petri dishes (90 mm). A 5 mm mycelial disc was cut from the edge of a 7-day-old *Botrytis cinerea* colony and placed in the center of each drug-containing PDA medium. The dishes were then incubated at 25 ± 1°C in the dark for 7 days. The inhibition rate was calculated by measuring the two vertical diameters (mm) of the colony using digital calipers, with three replicates for each treatment group. After incubation at 25 ± 1°C for 48 h, the lowest concentration that completely inhibited fungal growth (i.e., no visible mycelial growth) was defined as the minimum inhibitory concentration (MIC). Figure 1 As shown, no colony growth was observed within 48 h after incubation; therefore, the MIC for FA, FAM, and FAE was 800 mg / L. Table 1 shows the effects of FA, FAM, and FAE at a concentration of 800 mg / L on… B. dothideaThe inhibition rates were 68.76%, 80.93%, and 86.73%. Therefore, FAE inhibition... B. dothidea The colony expansion activity was significantly higher than that of FAM and FA.
[0029] Table 1. Effects of ferulic acid compounds on... B. dothidea Comparison of inhibition rates Five-mm diameter *Botrytis cinerea* mycelial cakes were transferred to potato dextrose liquid medium (PDB) and cultured for 2 days at 25°C using a constant temperature shaker at 120 r / min. Then, FA, FAM, and FAE were added to achieve concentrations of 0 (control) and 800 mg / L (MIC), respectively, and the culture continued for another day. Mycelia were collected by centrifugation at 4°C for 10 min at 10000×g, washed with sterile distilled water, and dried at 50°C. The dried mycelia were then weighed. Each treatment was repeated three times. The effects of FA, FAM, and FAE on the dry weight of the mycelia were determined by weighing the dried mycelia; the results are shown in Table 2. After treatment with 800 mg / L FA, FAM, and FAE, respectively, the dry weights of their mycelia were 0.0381 ± 0.00189 g, 0.0318 ± 0.0024 g, and 0.0227 ± 0.0003 g, respectively. The dry weights of the mycelia after FAE treatment were... B. dothidea The mycelial dry weight was significantly lower than that of FA and FAM.
[0030] Table 2. Effects of ferulic acid compounds on... B. dothidea Comparison of mycelial dry weight Example 2: Wall Material Screening Ethyl ferulic acid liposomes were prepared by melt emulsification and ultrasonication using solid and liquid oils as wall materials and ethyl ferulic acid as core material.
[0031] (1) Weigh the solid and liquid oils of the wall material (the first combination: 0.1 g cholesterol (solid) and 0.1 g soybean phosphatidylcholine (liquid), or the second combination: 0.1 g distearate (solid) and 0.1 g caprylate (liquid)) to prepare an oil mixture. Heat the oil mixture and 0.2 g ethyl ferulic acid in a tabletop closed electric furnace at 73±1℃ for 10~15 min until it melts. Keep it at this temperature to obtain the oil phase.
[0032] (2) Add Tween-80 to deionized water to make the final concentration 3% by mass, place it in a heat-collecting constant temperature magnetic stirrer and preheat it to 73±1℃, while stirring at 1000 rpm for 10 min to ensure that Tween-80 is evenly dispersed in water to obtain an aqueous phase.
[0033] (3) At 73 ± 1℃, 9.6 g of aqueous phase was slowly added dropwise to 0.4 g of oil phase and stirred for 10 min. The resulting mixture was transferred to a cell sonicator and ultrasonically dispersed for 10 min at a power of 250 W (5 s of sonication, 5 s interval) in a 73 ± 1℃ hot water bath. Then, it was cooled and solidified for 30 min in an ice water bath to obtain ethyl ferulic acid liposomes.
[0034] The particle size and polydispersity index (PDI) of ethyl ferulate liposomes prepared using two different wall materials (combination 1 or combination 2) were compared. The particle size and PDI were determined as follows: 0.06 mL of ethyl ferulate liposomes were placed in a centrifuge tube, and deionized water was added to a final volume of 7 mL for a dilution greater than 100-fold. The mixture was then gently shaken to ensure uniform dispersion. An appropriate amount of the diluted sample solution was added to a DTS1070 Malvern potential sample cell, and the average particle size and PDI were measured using a Malvern particle size analyzer. Each sample was measured three times in parallel at 25°C using a 90° angle, and the average value was taken. Encapsulation efficiency is a key indicator for evaluating the liposome embedding effect, while particle size and PDI reflect the uniformity and stability of liposome dispersion.
[0035] Table 3. Effects of different wall materials on particle size and polydispersity index of ethyl ferulic acid liposomes As shown in Table 3, compared with cholesterol and soybean phosphatidylcholine, distearate and caprylate glycerides have better encapsulation effect and uniformity as liposome wall materials, with an encapsulation rate of 95.46 ± 0.91%, a particle size of 124.8 ± 0.89 nm, and a PDI of 0.1685 ± 0.0005.
[0036] Example 3: Effect of ethyl ferulate concentration on the encapsulation efficiency of ethyl ferulate liposomes The preparation method of ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 0.25%-4% by mass.
[0037] Ethyl ferulic acid solutions with concentrations ranging from 2 to 16 μg / mL were prepared. The absorbance was measured at 326 nm using a UV-Vis spectrophotometer, and a standard curve for ethyl ferulic acid was plotted. Figure 2 (A in the middle).
[0038] Soak ultrafiltration centrifuge tubes in ultrapure water for at least 4 hours. Add an appropriate amount of ethyl ferulate liposomes to the ultrafiltration centrifuge tubes and centrifuge at 10,000 rpm for 40 minutes to remove water. Take 0.02 g of the supernatant liposomes, add 20 mL of anhydrous ethanol, and sonicate for 20 minutes to rupture the liposomes. Measure the absorbance at 326 nm using a UV-Vis spectrophotometer. Calculate the encapsulation rate of ethyl ferulate liposomes using the formula. from Figure 2 As shown in B, the encapsulation efficiency of ethyl ferulate liposomes increases with the increase of ethyl ferulate content, reaching a peak at 2% ethyl ferulate liposomes with an encapsulation efficiency of 96.69 ± 0.71%, and then decreasing. This is because the addition of liquid oil makes the lipid matrix more disordered, resulting in increased defects, structural distortion, and the creation of more space, forming an imperfect crystal structure. The low encapsulation efficiency of 4% ethyl ferulate liposomes may be because the NLP crystal structure has reached its upper limit in terms of the ability to accommodate active substances, and further increasing the amount of ethyl ferulate will not increase the encapsulation ability.
[0039] Example 4: Effect of ethyl ferulic acid concentration on the preparation of ethyl ferulic acid liposomes The liposomes of different concentrations of ethyl ferulic acid prepared in Example 3 were diluted 50 times, and the average particle size, dispersion index and potential of the samples were tested using a laser particle size analyzer.
[0040] from Figure 3 As can be seen, when the content of ethyl ferulate is 2% by mass, the ethyl ferulate liposomes are in a good overall state, with a particle size of 121.4 ± 0.96 nm, a PDI of 0.1754 ± 0.001, and a Zeta potential of -58.3367 ± 1.37 mV.
[0041] Example 5: Micromorphology of ethyl ferulic acid liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0042] Take 0.2 mg of ethyl ferulate liposomes into a centrifuge tube, add deionized water to 10 mL, dilute by more than 50 times, and shake appropriately to evenly disperse the ethyl ferulate liposomes in water. Then take an appropriate amount of liquid sample and drop it onto a copper grid, let it air dry at room temperature for 24 h, and observe its morphology using SEM.
[0043] like Figure 4As shown, the ethyl ferulate liposome nanostructures exhibit a spherical shape slightly smaller than 200 nm, with minimal size variation, uniform dispersion, non-aggregation, and a smooth surface, consistent with the results for particle size, PDI, and Zeta potential. Studies have shown that smaller nanoliposome particle sizes result in weaker van der Waals forces between the structures, thereby improving stability by inhibiting aggregation. Ethyl ferulate liposomes, with their relatively small particle size within the nanoliposome carrier system, not only possess excellent drug loading capacity but also exhibit significant anti-aggregation properties.
[0044] Example 6: X-ray diffraction (XRD) analysis of ethyl ferulic acid liposomes The preparation method of ethyl ferulate liposomes and nanoliposome carriers (NLP) in this embodiment is the same as in Example 2, using the second combination of wall materials; the amount of ethyl ferulate added to the ethyl ferulate liposomes is 2% by mass; ethyl ferulate is not added to the oil phase during the preparation of the nanoliposome carrier (NLP), and the mixing ratio of the oil phase and the aqueous phase is 0.2:9.8. XRD analysis of the liposomes was performed using an X-ray single-crystal diffractometer. Equal masses of ethyl ferulate and ethyl ferulate liposomes were placed on a glass slide, uniformly flattened, and then placed in the instrument for testing. Test conditions: tube voltage 40 kV, tube current 40 mA, Cu target wavelength 1.5406 Å, Co target wavelength 1.79026 Å, scanning range (2θ) 5° - 60°, scanning rate 2° / min, step size 0.013°.
[0045] from Figure 5 As can be seen, ethyl ferulate, as an element, possesses a relatively perfect crystal form, resulting in high, narrow, and sharp diffraction peaks. The main diffraction peaks appear at 13.22°, 16.11°, 20.75°, 26.62°, and 28.14°, which are characteristic diffraction peaks of ethyl ferulate. The diffraction patterns of ethyl ferulate-supported nanostructured liposomes (FAE-NLP) and nanoliposome carriers (NLP) are extremely similar, with broad and low diffraction peaks consistent with the non-crystalline characteristics of amorphous powders. Two relatively strong diffraction peaks appear at 19.39° and 22.97°, and 19.55° and 22.89°, respectively. However, compared to the diffraction peaks of NLP, the sharpness of the ethyl ferulate liposome diffraction peaks decreases, while the peak width increases. This may be because after ethyl ferulate enters the NLP cavity, its molecular structure undergoes subtle changes, forming a new phase. Furthermore, the characteristic peaks of ethyl ferulate have completely disappeared in the peaks of ethyl ferulate liposomes, indicating that ethyl ferulate has been successfully encapsulated in the nanostructured liposome carrier.
[0046] Example 7: Thermogravimetric (TGA) Analysis of Ethyl Ferulic Acid Liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0047] The thermal stability of ethyl ferulic acid liposomes was analyzed using a thermogravimetric analyzer (TGA, Mettler TG-DSC 3+). The sample and empty crucible were weighed, and the crucible containing the sample was placed on the thermogravimetric instrument support. The furnace was closed, and the analysis was performed under a nitrogen atmosphere with a heating rate of 10 °C / min from 25 °C to 500 °C.
[0048] Depend on Figure 6 It can be seen that the TGA curve ( Figure 6 A) and DTG curve ( Figure 6 Section B) illustrates the weight change of the samples and the relationship between the rate of weight change and temperature. The TGA and DTG curves of ethyl ferulate show two distinct thermal degradation processes. The first stage occurs below 100℃, exhibiting very small mass loss due to surface water evaporation. The second stage, from 154℃ to 240℃, shows significant mass loss, with the fastest decomposition rate at 230℃, until approximately 245℃ when most of the ethyl ferulate has degraded, leaving a residual mass of 11.51%. The TGA and DTG curves of ethyl ferulate liposomes show significant mass loss from 200℃ to 420℃, with most NLPs degrading around 420℃, leaving a residual mass of 14.54%. The TGA and DTG curves of NLP showed that within the temperature range of 0℃ to 600℃, NLP exhibited two stages of mass change. Significant mass loss occurred from 200℃ to 350℃, and the rate of mass loss accelerated starting at 330℃, until most of the ethyl ferulate liposomes degraded at 480℃, with a residual rate of 8.53%. Notably, the residual rate of NLP was lower than that of ethyl ferulate liposomes throughout the entire heating phase, but above 430℃, its residual rate was even lower than that of ethyl ferulate. This is because the nanostructured liposome carrier is composed of a mixture of solid and liquid fats, which themselves degrade under ultra-high temperature conditions. However, after encapsulating ethyl ferulate, its mass loss decreased and the residual rate increased. This is related to the strong interaction between ethyl ferulate and NLP, and ethyl ferulate can also alter the structural morphology of NLP, thereby preventing the degradation of ethyl ferulate. This phenomenon indicates that ethyl ferulate was successfully encapsulated in NLP, and the successful preparation of ethyl ferulate liposomes improved the stability of both ethyl ferulate and the liposome structure.
[0049] Example 8: Fourier Transform Infrared (FT-IR) Spectroscopy Analysis of Ethyl Ferulic Acid Liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0050] The infrared absorption spectra of ethyl ferulic acid liposomes were detected using FT-IR. An appropriate amount of sample (FAE-NLP, NLP, or FAE) and 100 mg of potassium bromide reagent were mixed and ground thoroughly. The mixture was then compressed into tablets at 20 MPa, followed by infrared spectroscopy. The wavenumber range was 400–4000 cm⁻¹. -1 The spectrometer has a resolution of 4 cm⁻¹. -1 The signal-to-noise ratio was 50,000:1, and each sample was scanned 32 times.
[0051] like Figure 7 As shown in the FT-IR spectrum of pure ethyl ferulic acid, at 3178 cm⁻¹... -1 The absorption peak at 3069 ~ 2991 cm⁻¹ corresponds to the stretching vibration of the hydroxyl group (OH) in ethyl ferulic acid. -1 The absorption peak corresponds to the stretching vibration of the benzene ring and the CH bond on C=C in the ethyl ferulic acid molecule, at 1678 cm⁻¹. -1 ~ 1443cm -1 The nearby absorption peak corresponds to the stretching vibration of the carbonyl group (C=O) of ethyl ferulic acid ester to the carbon-carbon double bond (C=C) in the benzene ring skeleton. This can be seen in the NLP FT-IR spectrum at 1742 cm⁻¹. -1 There is a distinct peak, corresponding to the characteristic absorption peak of C=O. The FT-IR spectrum of ethyl ferulic acid liposomes shows a very similar trend to that of NLP, with almost identical frequencies of stretching vibrations of the major functional groups, around 1742 cm⁻¹. -1 The characteristic absorption peak of C=O is also present, and the peak value is enhanced. However, the characteristic absorption peak of pure ethyl ferulate in the spectra of NLP and ethyl ferulate liposomes shifts or disappears, indicating that ethyl ferulate is successfully embedded in the nanoliposome structure, causing changes in the structure and chemical bonds of NLP, such as weakening or slight shifting.
[0052] Example 9: Physical stability of ethyl ferulic acid liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0053] Five mL of ethyl ferulic acid liposomes were placed in centrifuge tubes and stored in ovens at 45°C, 25°C, and refrigerators at 4°C for 30 days, respectively. After removal, the tubes were allowed to stand at room temperature for 6 hours, centrifuged at 8000 rpm for 15 minutes, diluted 50 times, and their average particle size, dispersion index, and potential were measured. The results were used to analyze their stability and to determine the antibacterial stability of the samples.
[0054] like Figure 8 As shown, NLPs were observed to be uniformly milky white and translucent to the naked eye, while ethyl ferulate liposomes were pale yellow. After shaking, the layers were uniform and evenly distributed, with no visible precipitates or particles in the entire system. After 30 days of storage at different temperatures, the NLPs at the three temperatures did not change significantly, but the color of the ethyl ferulate liposomes darkened significantly, with the liposomes at 45℃ showing the greatest change, turning a milky yellow color. No stratification or precipitation / flocculation was observed in any of the treatment groups.
[0055] The microscopic changes are shown in Table 4. The particle sizes of ethyl ferulate liposomes after storage at 4℃, 25℃ (room temperature), and 45℃ for 30 days were 129.57 ± 1.12 nm, 130.27 ± 1.63 nm, and 139.77 ± 6.91 nm, respectively. Compared with day 0 (129.20 ± 3.86 nm), the particle size of ethyl ferulate liposomes at 4℃ and 25℃ did not change significantly, while the particle size of liposomes stored at 45℃ increased slightly, but still maintained a low average particle size. During the entire storage process, the PDI decreased slightly, but remained within the range of 0.16 ~ 0.20; the Zeta potential increased slightly during storage, but the fluctuation range was also small, with the absolute value consistently remaining between 48.64 mV and 57.57 mV. The results of the antibacterial experiment showed that the antibacterial activity of ethyl ferulate liposomes did not change much after 30 days of storage at different temperatures, decreasing from 90.04% to 88.54% (4℃), 86.53% (25℃) and 84.67% (45℃).
[0056] Table 4. Temperature stability results of ethyl ferulate liposomes Example 10: In vitro release of ethyl ferulic acid liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0057] The amount of ethyl ferulic acid released from ethyl ferulic acid liposomes was measured using dialysis.
[0058] Preparation of receiving cells: Ethanol and PBS solution at a volume ratio of 7:3 were added to a beaker and stirred thoroughly with a magnetic stirrer to form an ethanol-PBS solution. A 50% (v / v) ferulate liposome-ethanol solution and a ferulate ethyl ethanol solution were prepared using the ethanol-PBS solution. The ferulate ethyl liposome-ethanol solution (FAE-NLP group) was placed in one dialysis bag, and the same concentration of ferulate ethyl ethanol solution (FreeFAE group) was placed in another dialysis bag. The bags were then clamped and placed in the two receiving cells respectively. The supernatant from the receiving cells was collected at 1 h, 3 h, 6 h, 12 h, 24 h, and 48 h, and its absorbance at 326 nm was measured.
[0059] As shown in Table 5 and Figure 9 As shown, the FAE-NLP group released 40.53% of ethyl ferulate within the first 4 hours, while the FreeFAE group released 83.4% within the same timeframe. Throughout the in vitro release period, the cumulative release rate and speed of ethyl ferulate in the FreeFAE group were consistently higher than those in the FAE-NLP group. At 24 hours, the cumulative release rate of ethyl ferulate in the FreeFAE group was 92.83%, while the cumulative release rate in the FAE-NLP group was 64.17% within the same timeframe. The rapid initial release was followed by a slower release, indicating that ethyl ferulate liposomes have a sustained-release effect.
[0060] Table 5 Comparison of ethyl ferulate release rates before and after preparation of ethyl ferulate liposomes Example 11: In vitro antibacterial activity of ethyl ferulic acid liposomes The preparation method of the ethyl ferulic acid liposomes in this embodiment is the same as in Example 2, using the second combination of wall materials, and the amount of ethyl ferulic acid added is 2% by mass.
[0061] The effect of ethyl ferulate liposomes on the mycelial growth of *Staphylococcus aureus* (China Industrial Microbial Culture Collection Center, strain accession number: CPCC 810148) was determined using the agar dilution method. First, ethyl ferulate (concentration 800 mg / L) and ethyl ferulate liposomes (concentrations of 0% (control group, CK), 0.25%, 0.5%, 1%, and 2%) were added to sterilized PDA medium cooled to approximately 50°C to prepare drug-containing PDA cultures. Then, the drug-containing PDA medium was poured into sterile Petri dishes, cooled and solidified, and 5 mm mycelial discs were cut and placed upside down in the center of the drug-containing PDA medium. After culturing for 7 days, the colony diameter was measured using calipers. Table 6 and... Figure 10 The effects of different dosages of ethyl ferulic acid liposomes on... B. dothideaEffect of ethyl ferulate on mycelial growth. The results showed that the antibacterial activity increased with increasing ethyl ferulate concentration. The strongest antibacterial activity was observed at a 2% ethyl ferulate liposome concentration (400 mg / L ethyl ferulate), with a colony diameter of 8.86 ± 0.82 mm and an inhibition rate of 90.15 ± 0.90%, which was higher than that of the 800 mg / L ethyl ferulate technical grade (colon diameter 21.77 ± 0.96 mm, inhibition rate 75.81 ± 1.06%). This indicates that encapsulation of ethyl ferulate can increase its antibacterial activity because nanostructured liposomes can improve the solubility of hydrophobic active substances.
[0062] Table 6. Effects of ethyl ferulate liposome preparation before and after preparation B. dothidea Comparison of mycelial growth
Claims
1. A method for preparing ethyl ferulic acid liposomes, characterized in that, Includes the following steps: S1. Solid oil, liquid oil and ethyl ferulic acid are heated at 73±1℃ for 10-15 min until they melt, and kept at this temperature to obtain the oil phase; the mass ratio of the solid oil, liquid oil and ethyl ferulic acid is 1:1:0.25-4. S2. Prepare a 3% (w / w) Tween-80 aqueous solution, heat it to 73±1℃ and stir at 1000 rpm for 10 min to obtain the aqueous phase; S3. At 73±1℃, 9.4-9.775 parts by weight of aqueous phase were added dropwise to 0.225-0.6 parts by weight of oil phase, stirred for 10 min, ultrasonically dispersed for 10 min, and then cooled and solidified in an ice bath for 30 min to obtain ethyl ferulic acid liposomes.
2. The method according to claim 1, characterized in that, Includes the following steps: S1. Solid oil, liquid oil and ethyl ferulic acid are heated at 73±1℃ for 10-15 min until they melt, and kept at this temperature to obtain the oil phase; the mass ratio of the solid oil, liquid oil and ethyl ferulic acid is 1:1:
2. S2. Prepare a 3% (w / w) Tween-80 aqueous solution, heat it to 73±1℃ and stir at 1000 rpm for 10 min to obtain the aqueous phase; S3. At 73±1℃, 9.6 parts by weight of aqueous phase were added dropwise to 0.4 parts by weight of oil phase, stirred for 10 min, ultrasonically dispersed for 10 min, and then cooled and solidified in an ice bath for 30 min to obtain ethyl ferulic acid liposomes.
3. The method according to claim 1, characterized in that, The solid oil is cholesterol or distearate, and the liquid oil is soybean phosphatidylcholine or caprylate.
4. The method according to claim 3, characterized in that, The solid oil is glyceryl distearate, and the liquid oil is glyceryl caprylate.
5. A ferulic acid ethyl ester liposome prepared by the method according to any one of claims 1-4.
6. An antibacterial agent with ethyl ferulic acid liposomes as the active ingredient as described in claim 5.
7. The antibacterial agent according to claim 6, characterized in that, The concentration of ethyl ferulic acid plasmid is 0.25%-2% by mass.
8. The antibacterial agent according to claim 7, characterized in that, The concentration of ethyl ferulic acid plasmid was 2% by mass.
9. The use of the ethyl ferulic acid liposome of claim 5 or the antibacterial agent of claim 6 in the treatment of soft rot in kiwifruit.
10. The application according to claim 9, characterized in that, The application of the ethyl ferulic acid liposomes of claim 5 or the antibacterial agent of claim 6 in inhibiting *Botrytis cinerea*, wherein *Botrytis cinerea* is the pathogen of soft rot in kiwifruit.